Confessions of a Bi-Polar Mardi Gras Queen - Etienne Marie (Alluvium Books, 2009)
Marie Etienne's first memoir, STORKBITES, was praised by the San Francisco Chronicle Book Review as a compelling memoir . . . Etienne's writing is fresh; her epiphany is clear, her ending is powerful and satisfying. Now she returns with a collection of outrageous true stories that are fast-paced, heartfelt, and brutally honest.